Survey of the DASH7 Alliance Protocol for 433 MHz Wireless Sensor Communication - Maarten Weyn; Glenn Ergeerts; Luc Wante; Charles Vercauteren; Peter Hellinckx (International Journal of Distributed Sensor Networks)
433 MHz is getting more attention for Machine-to-Machine communication. This paper presents the DASH7 Alliance Protocol, an active RFID alliance standard for 433 MHz wireless sensor communication based on the ISO/IEC 18000-7. First, the major differences of 433 MHz communication compared to more frequently used frequencies, such as 2.4 GHz and 868/920 MHz are explained. Subsequently, the general concepts of DASH7 Alliance Protocol are described, such as the BLAST networking topology and the different OSI layer implementations, in a top-down method. Basic DASH7 features such as the advertising protocol, ad-hoc synchronization and query based addressing are used to explain the different layers. Finally, the paper introduces a software stack implementation named OSS-7, which is an open source implementation of the DASH7 alliance protocol used for testing, rapid prototyping, and demonstrations.